2010
DOI: 10.5248/111.337
|View full text |Cite
|
Sign up to set email alerts
|

New combinations in <I>Raffaelea</I>, <I>Ambrosiella</I>, and <I>Hyalorhinocladiella</I>, and four new species from the redbay ambrosia beetle, <I>Xyleborus glabratus</I>

Abstract: Female adults of the redbay ambrosia beetle, Xyleborus glabratus (Coleoptera: Curculionidae: Scolytinae), from the southeastern USA were individually macerated and serially diluted onto culture media for isolation of fungal symbionts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 33 publications
3
119
1
4
Order By: Relevance
“…This contradicts the MP results of Harrington et al (2010) based on LSU data but is consistent with those based on the SSU data. These discrepancies could be due to differences in taxon sampling, the loci that were used, and the methodologies used to define these relationships (MP vs. ML).…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…This contradicts the MP results of Harrington et al (2010) based on LSU data but is consistent with those based on the SSU data. These discrepancies could be due to differences in taxon sampling, the loci that were used, and the methodologies used to define these relationships (MP vs. ML).…”
Section: Discussioncontrasting
confidence: 57%
“…This LSU MP analysis found Raffaelea as defined by Harrington et al (2010) to be monophyletic, as did their LSU MP analysis. Where as, the ML (LSU, SSU and BT) analyses (Fig S2-S4) as well as the ML, BI and MP analyses using the combined data sets, in this study, found Raffaelea spp.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations